Сарненський укріпрайон напередодні та на початку Другої світової війни - Юрчук, Людмила; Iurchuk, L. (Волинський національний університет імені Лесі Українки, 2012)
На основі архівних матеріалів, наукових праць польських істориків, мемуарів, польської преси, спогадів сучасників подій здійснено спробу дослідити значення Сарненського укріпрайону в оборонній стратегії Другої Речі Посполитої. On the basis of the archival materials, scientific researches of polish historians, also recollections of the contemporaries as well as the polish press the author makes an attempt to investigate the importance of the Sarnenskiy fortification area in the defensive strategy of Poland.
Sarnenskij Fortification оn the Eve and in the Beginning оf World War II
Keywords: Друга Річ Посполита; Сарненський укріпрайон; Корпус охорони прикордоння; батальйон КОП; Polish State; the Polish Frontier Defense Corps; Sarnenskiy fortification; fortifications